2023
DOI: 10.21873/cgp.20368
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative Breast Cancer: Identification of circRNAs With Efficacy in PreclinicalIn VivoModels

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY-NC-ND) 4.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 164 publications
0
10
0
Order By: Relevance
“…Therefore, acquired resistance to paclitaxel is undoubtedly the biggest obstacle in improving the overall response and survival of patients with TNBC. In recent years, owing to the stability and abundance of circRNAs, an increasing number of circRNAs have been identi ed as abnormally expressed in TNBC; as important regulators of TNBC cancer progression, circRNAs are of great signi cance for the resistance of TNBC [9,19]. However, research on circRNAs associated with paclitaxel resistance in TNBC remains limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, acquired resistance to paclitaxel is undoubtedly the biggest obstacle in improving the overall response and survival of patients with TNBC. In recent years, owing to the stability and abundance of circRNAs, an increasing number of circRNAs have been identi ed as abnormally expressed in TNBC; as important regulators of TNBC cancer progression, circRNAs are of great signi cance for the resistance of TNBC [9,19]. However, research on circRNAs associated with paclitaxel resistance in TNBC remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages, compared to lncRNAs and miRNAs, have the potential to be ideal biomarkers for the treatment of cancer diseases [8]. Many studies have demonstrated that abnormal expression of circRNAs is inextricably linked to tumorigenesis and chemical resistance in TNBC [9,10]. For example, Zheng et al reported that CircGFRA1 affects the sensitivity of TNBC cells to paclitaxel [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that E3 ligases, including SYVN1 can have opposite effects as either tumor suppressors (TS) or oncogenes depending on the context or type of cancer ( 73 75 ). With regards to SYVN1, previous studies have shown that it functions as a tumor suppressor in breast ( 37 , 39 , 41 , 76 , 77 ) and ovarian ( 40 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) [40] Circ-HER2 [41] Circ-TADA2A-E6 [42] Has-circ-0025202 Breast cancer (BC) [43] Circ-Dnmt1 [44] Circβ-catenin Hepatocellular carcinoma (HCC) [45] Circ-RNA-104718 [46] Circ-TRIM33-12 [47] Circ-RNA 100146 Non-small cell lung cancer (NSCLC) [48] Circ-PTPRA [49] Table 2. Cont.…”
Section: Circ-agfg1mentioning
confidence: 99%